Does eligibility requirements matter for academic achievements? A quasi-experimental retrospective study of students studying intermediate statistics - Nicklas Pettersson; Niklas Karlsson; Daniela Andrén (Örebro University School of Business, 2023)
Student achievements are expected to be affected by both educational activities and learning during a course and previous teaching and learning, and earlier eligibility requirements. Using data from a quasi-experimental retrospective study, we estimated the effect on exam scores in an intermediate course in statistical theory from both earlier eligibility requirements, the realignment of a prerequisite course in introductory statistics and students' characteristics. We found that success in intermediate statistics was explained by the realignment and eligibility requirements in Mathematics, and also by the intersection between gender and foreign background.
Keywords: A22; I20; I21; 330; statistics education; aligned course; eligibility requirements; academic evaluation; quasi-experimental retrospective design